The Journey Towards the Trouts: Put na Plitvice by Adolf Veber Tkalčević. The Text-Formative Role of Culinary Motifs - Pieniążek-Marković, Krystyna (Poznańskie Studia Slawistyczne, 2022)
Adolfo Veber Tkalčević (1825–1889) a Croatian philologist, writer, passionate traveler and a Catholic clergyman is the author of the first Croatian account of the travel to the Croatian “Lake District” Put na Plitvice (Road to Plitvice, 1860). As a travel narrative, this book has a “worldbuilding” potential, introducing the Plitvice Lakes to Croatian culture, to the national landscape. In this article,Ifocus on the culinary theme of the trip. One of its side goals was savouring the trouts, but throughout the entire trip the tables of wanderers did not want to fill with them, offering the text-forming abundance instead. The journey “around the empty table” is a kind of self-portrait of “explorers” ready for a “heroic” attitude for the common good. Bearing in mind the specificity of Croatian Romanticism, which this work represents, I read the text in a cultural, anthropological and identity context, referring to the classics of discourse, and devoting less attention to travel studies.